Digitised methods of library services - Singh, Pramod Kumar (Shree, 2004)
Contents of material: 1/ Public library resource development. 2/ Preservation of library materials. 3/ Information retrieval. 4/ Archiving. 5/ Librarians in user services. 6/ Issues and trends. 7/ Future of digital libraries.